Morfoanatomia de Barcella odora (Trail) Drude (Arecaceae: Arecoideae) ocorrente em ambiente de campinarana do PARNA Viruá - Da Cruz, Pedro Cavalcante (Instituto Nacional Pesquisas da Amazônia - INPA, 2024)
The Arecaceae family is diverse across the tropics and subtropics, but lacks morphoanatomical studies to understand its relationship with the environment. The objective of the study was to characterize the morphonatomy of vegetative and reproductive organs of Barcella odora by comparing their structure in different environmental conditions. The study was carried out in the vegetation of Campinara do PARNA do Viruá, Caracaraí, Roraima. For the general morphoanatomy of the species, two individuals were collected using the destructive method, observing the underground system, two inflorescences and two infructescences. For anatomical studies, samples were collected from the rachis, petiole and pinnules from the middle third of the apex, middle and base of the leaf. Comparative morphometry of the species was carried out, living in two areas with different microclimatic conditions: one with more open vegetation, lower relief and affected by fire (Area 1) and the other, close to the edge of the forest, higher relief and not affected by fire (Area 2). For each area, 10 individuals were selected and from each one two live, green leaves where the length and width of the petiole, rachis and pinnules were measured. Stomatal density was also performed for both microenvironments. The underground system is cylindrical with adventitious roots extending throughout its length. The underground sheaths and part of the petiole have hair covering them, protecting the apical meristems and inflorescences in the initial stage of development. The aerial system has a planoconvex petiole and pinnate limbus. The inflorescence is a panicle organized in triads with two staminate flowers and one pistillate at the base of the rachille and in the distal portion only dyads of staminate flowers. The ripe fruits are oblong, with a smooth, orange-colored epicarp, a fleshy, fibrous mesocarp and a rigid, sclerified, blackened endocarp that protects one to three seeds; it has three germinal pores and is strongly attached to the brown integument. The endosperm is white and rigid and in the portion located close to the pores there is an elongated beige embryo with one of the flat ends. Leaf morphometric averages varied between environments. The average stomatal density also varied between the two environments, being higher in the area affected by the fire. The adventitious roots have anatomical characteristics similar to other palm trees. The petiole and rachis have similar anatomical configuration. The pinnules have a thick cuticular stratum, epidermis with straight periclinal walls, hypodermis and expansion cells on both sides, dorsiventral mesophyll with vascular bundles of different calibers. The morphoanatomical, qualitative and quantitative characteristics express the adaptations of Barcella odora to the campinarana environment, indicating phenotypic plasticity for adaptation to different environmental conditions.
Keywords: Palmeiras; Sistema subterrâneo; Microambientes